The Impact of Increased Maternal sFlt-1/PlGF Ratio on Motor Outcome of Preterm Infants - Middendorf, Lisa; Gellhaus, Alexandra; Iannaccone, Antonella; Köninger, Angela; Dathe, Anne-Kathrin; Bendix, Ivo; Reisch, Beatrix; Felderhoff-Mueser, Ursula; Huening, Britta (Frontiers in Endocrinology, 2022)
Background: The sFlt-1 (soluble fms-like tyrosine kinase-1)/PlGF (placental growth factor) ratio serves as a clinical biomarker to predict the hypertensive, placenta-derived pregnancy disorder pre-eclampsia often associated with placental dysfunction and fetal growth restriction. Additionally elevated levels also increase the risk for prematurity. However, its predictive value for subsequent neurological outcome has not been investigated. Objective: This study aimed to evaluate the correlation of maternal sFlt-1/PlGF ratio with early motor outcome of preterm infants. Design/Methods: Single center study including 88 preterm infants born at a gestational age ≤ 34+0 between February 2017 and August 2020 with available maternal sFlt-1 and PlGF levels and general movement assessment of the infant at the corrected age of 3 to 5 months. Infants were stratified into high and low ratio groups according to a maternal sFlt-1/PlGF cut-off value of 85. To investigate the early motor repertoire and quality of spontaneous movements of the infant, the Motor Optimality Score (MOS-R) based on antigravity movements and posture patterns, was applied with special attention to the presence of fidgety movements. Linear regressions were run to test differences in infants motor repertoire according to the maternal sFlt-1/PIGF ratio. Results: Linear regression analysis showed that the sFlt-1/PlGF ratio does not predict the MOS-R score (β=≤0.001; p=0.282). However, children with a birth weight below the 10th percentile scored significantly lower (mean 20.7 vs 22.7; p=0.035). 91% of these children were in the group with an increased ratio, which in turn is a predictor of low birth weight (β= -0.315; p <0.001). In the group with high sFlt-1/PLGF ratios above 85, mothers of female infants had lower average sFlt-1/PlGF ratio compared to mothers of male infants (median: 438 in female vs. 603 in male infant, p=0.145). Conclusions: In our cohort, low birth weight significantly correlated with an elevated sFlt-1/PlGF ratio and had a negative effect on the outcome in the MOS-R. A direct correlation between an increased ratio and adverse motor outcome (MOS-R) at the age of 3-5 months was not demonstrated.